“Role of Government Welfare Programes and Employee Engagement in MSMEs: A case of North Karnatka region, India” - G. S, Hiremath; Banakar, Vinayak; Belur , Jayanti (International Journal of Psychosocial Rehabilitation, 2020)
Employee Engagement is a significant activity in organizations. The focus of this paper is to know the relationship between employee engagement activity and government welfare programs. This study is of interest as the government's policy on employees of MSME has made a significant influence on employees. Hence, the objective of paper is to determine whether an association exists between employee engagement activities carried out by MSME and policies of the Government. The study adopts a qualitative and quantitative approach. A structured questionnaire is distributed among respondents who are employees of MSMEs identified through snowballing. Data collected is processed and analyzed through IBM SPSS and a chi- square test is performed. Results indicate government policies and employee engagement activities are correlated. Interpretive Structural Modeling has been used to identify the relationship between factors affecting Employee Engagement. The study revealed that creating the willingness among employees about assisting the organization during crisis is crucial to the productivity of the organization.